Sustainable green construction management: schedule performance and improvement - Bon-Gang Hwang; Lay Peng Leong; Young-Ki Huh (Technological and Economic Development of Economy, 2014)
Over the last few years, the green building movement in Singapore has leaped bountifully. While environmental sustainability for greener construction has been emphasized, rare research has been conducted to analyze performance of green construction projects. As a result, this study aims to address schedule performance of green building construction projects and to provide some recommendations that may improve the targeted performance. To achieve this objective, a questionnaire was developed and the responses from 30 companies were analysed, and interviews with 6 project managers were conducted to further supplement and substantiate the survey results. The analysis reported that green building projects required an average of 8% more time than traditional building projects of similar size and characteristics. In addition, on average, these projects were delayed by 4.8% when compared with their as-planned schedules. Lastly, a list of recommendations was also introduced, aiming to ameliorate the schedule performance. This study will offer a benchmark for the industry to gauge the overall duration and performance of green building construction projects.